Overview of nominal compounds in Old Latvian - Bukelskytė-Čepelė, Kristina (Baltistica, 2020)
This article gives an overview of nominal compounds present in Old Latvian texts and dictionaries of the 17th century and analyses their characteristic properties. The results show that the well-attested categories of Baltic compounds are richly represented in Old Latvian texts. Distinctions between the different types of compounds are clearly indicated in terms of the formal properties of the components. It is proposed that a portion of the linking elements that are mostly used in the determinative compounds in Old Latvian might have originated from the original stem vowels of the first components. This Baltic model of coining compounds still attested in Old Latvian texts is no longer visible in Modern Latvian. Finally, it is also shown that the compositional suffix -is (m.)/-e (f.) generally used in possessive compounds and verbal governing compounds was originally restricted to adjectival compounds in Latvian.